Surgeon Satisfaction with Flexible Ureterorenoscopy and Laser Lithotripsy: A Comparison between General Anaesthesia and Combined-Spinal Anaesthesia - , Fiekabo Hart; , Furo Orupabo (Archives of Current Research International, 2025)
Aim: Comparing the effect of General Anaesthesia (GA) and combined Spinal Epidural Anaesthesia (CSE) on the comfort of the surgeon and flexible Ureterorenoscopy outcomes. Materials and Methods: Duration of study was 2 years, in a randomized prospective pattern. Sample size was 34, GA (n=17) and CSE (n=17). Analysis was on demographic, and perioperative parameters of patients. Results: 34 randomized patients were included with ASA I and II, no difference in demographic variable. Monitoring vital signs intraoperatively, 3 patients in CSE group had bradycardia, and hypotension which was significant when compared with GA group, bradycardia (p=0.002), hypotension (p=0.001). Additionally, 1 patient in CSE group experienced mucosal tears, but no complications observed in the GA group (p=0.006) statistically significant. The postoperative evaluation of surgeon comfort was statistical significance in favour of the GA group (p=0.001). Conclusion: GA and CSE are equally effective and safe Anaesthesia methods for f-URS procedures. Although regional anaesthesia may be preferred by the Anaesthesiologist, to avoid polypharmacy, and airway manipulation, the surgeon’s satisfaction is paramount, therefore general anaesthesia is preferred with less side effect as the CSE group showed statistical significance in bradycardia and mucosal injury and decreased surgeon comfort during surgery.